2018
DOI: 10.1177/1354816618785536
|View full text |Cite
|
Sign up to set email alerts
|

Offshoring of services as a competitive strategy in the tourism industry

Abstract: The offshoring of services has steadily expanded in recent years and acquired growing importance in certain tourism subsectors. The present study analyses for the first time the offshoring indices and the trend seen in tourism services, based on input–output data (Spanish National Accounts) during the 2000–2007 expansive period. A distinction is made between offshoring associated with international fragmentation of production and offshoring due to a shift from domestic to foreign suppliers. The results point t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…This study analyses for the first time the offshoring indices and the trend observed in tourism services based on I/O Data (Spanish national accounts) during the expansive period 2000-2007. There is a distinction between offshoring associated with international fragmentation of production and offshoring through the transition from Ukrainian to foreign suppliers. The results indicate the movement of intermediate services to foreign countries in certain tourism sub-sectors (including travel agencies and air and sea transport), which implies both international fragmentation of production and replacement of the source of supply (Fuster et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…This study analyses for the first time the offshoring indices and the trend observed in tourism services based on I/O Data (Spanish national accounts) during the expansive period 2000-2007. There is a distinction between offshoring associated with international fragmentation of production and offshoring through the transition from Ukrainian to foreign suppliers. The results indicate the movement of intermediate services to foreign countries in certain tourism sub-sectors (including travel agencies and air and sea transport), which implies both international fragmentation of production and replacement of the source of supply (Fuster et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Following the methodology initially proposed by Hanson (1996, 1999), in order to measure the level of offshoring, an indicator is defined as the proportion of imported inputs (II) over total inputs, both domestic and imported (TI). In subsequent studies, the indicator used to measure offshoring is defined as the proportion of imported inputs (II) over the value of production (Y) (Campa and Goldberg, 1997;Díaz Mora et al, 2007;Cadarso et al, 2012;Michel and Rycx, 2012;Castellani et al, 2013;Fuster et al, 2018Fuster et al, , 2019.…”
Section: Methodology and Datamentioning
confidence: 99%
“…Analogically, we can analyse whether reshoring is the result of a replacement of foreign suppliers with domestic suppliers or with in-house production within the company. This breakdown of the index has been used to analyse the phenomenon of offshoring (Díaz Mora et al, 2007;Castellani et al, 2010;Martínez-Mora, 2013 andFuster et al 2018) and reshoring (Fuster et al, 2020) but it has not yet been used to analyse the phenomenon of reshoring of services for the tourism sector.…”
Section: Reshoring Of Services To Replace Foreign Suppliers With Dome...mentioning
confidence: 99%
See 1 more Smart Citation
“…This phenomenon has been studied for goods and for certain service activities but has remained largely unnoticed in tourism studies. The paper by Fuster et al (2018) provides insights regarding the trends in offshoring in the service sector in Spain over the 2000–2007 period, with a particular focus on tourism-related activities. The authors explain how offshoring can be measured and monitored at the macro level through the use of various indices based on data coming from Input–Output tables.…”
mentioning
confidence: 99%